Diabetisches Fußsyndrom – Teil 2. Revaskularisation, Behandlungsalternativen, Versorgungsstrukturen, Rezidivprophylaxe - Rümenapf, G.; Morbach, S.; Rother, Ulrich; Uhl, C.; Görtz, H.; Böckler, D.; Behrendt, C. A.; Hochlenert, D.; Engels, G.; Hohneck, A.; Sigl, M. (Chirurg, 2020)
Diabetic foot syndrome (DFS) is the most frequent reason for major amputations in Germany. The majority of foot lesions are triggered by repetitive pressure in diabetic polyneuropathy. Peripheral arterial occlusive disease (PAOD) impairs wound healing and is the main risk factor for amputations. The treatment of wounds and infections as well as timely revascularization are decisive. The use of endovascular and vascular surgical methods depends on the distribution pattern and length of the occlusion processes. Both procedures are complementary. Bypass surgery is of great importance for neuroischemic DFS. Multidisciplinary centers that provide revascularization in DFS can achieve an improvement of arterial blood flow in 90% of the cases and reduce the amputation rate by up to 80%. Due to the high recurrence rate of diabetic foot lesions, measures for secondary prophylaxis are of exceptional importance (podological and orthopedic technical care, foot surgery).
CRIS-Team Scopus Importer:2020-12-04
Keywords: Foot surgery; Peripheral arterial occlusive disease; Secondary prophylaxis; Vascular surgery; Wound treatment